Case report Diagnostic and therapeutic difficulties in nasal-type NK/T-cell lymphoma – a case report - Sokołowska-Wojdyło, Małgorzata; Sikorska, Monika; Roszkiewicz, Jadwiga (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Extranodal NK/T-cell lymphoma, nasal type occurs more frequently in Asia and Central America and is undoubtedly associated with Epstein-Barr virus. The skin is the second most common site of involvement after the nasal cavity and nasopharynx. Clinically papulonodular lesions are observed on the trunk, limbs or face, within which decay often occurs. The characteristic histological features concern an angiocentric and angiodestructive growth pattern. In most cases the lymphoma cells have the immunophenotype of NK cells: CD2(+), CD45RO(+), CD43(+), CD56(+), TCRαβ(–) and TCRγδ(–). Surface antigen CD3 is usually absent, although its cytoplasmic form (cCD3) is detected. The clinical course of this disease is very aggressive, and although successful treatment has not been developed yet, a first-line treatment, recommended in the early stages of the disease, is radiotherapy. Chemotherapy is recommended for advanced forms of NK/T-cell lymphoma, but usually results in short remissions. In this paper we describe the clinical course of extranodal NK/T-cell lymphoma, primary extranasal. The patient presented with growing cheek oedema with signs of infiltration involving swelling of both eyelids, leading to their necrosis. Moreover, in the extremities there were single lesions of erythematous infiltrated type present. Diagnosis of extranodular NK/T-cell lymphoma nasal type was the result of histopathological examination of the skin. Despite an initially good response to chemotherapy, the patient died after the second treatment cycle due to staphylococcal sepsis.